2001
DOI: 10.1039/b103111m
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cyclisation of cinnamyl ethers mediated by CAN: a stereoselective synthesis of 3,4-trans disubstituted tetrahydrofuran derivatives

Abstract: The oxidative cyclisation of cinnamyl ethers mediated by cerium(IV) ammonium nitrate results in the stereospecific formation of 3,4-trans disubstituted tetrahydrofuran derivatives in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Thus, the reaction of trimethoxycinnamyl cinnamyl ether with CAN in methanol resulted in the stereoselective formation of the corresponding 3,4-trans-disubstituted tetrahydrofuran derivative in moderate yield. A marginal increase in the yield was noticed when the reaction was done under an oxygen atmosphere (Scheme ) 17 …”
Section: Reactions Involving Carbon−carbon Bond Formationmentioning
confidence: 99%
“…Thus, the reaction of trimethoxycinnamyl cinnamyl ether with CAN in methanol resulted in the stereoselective formation of the corresponding 3,4-trans-disubstituted tetrahydrofuran derivative in moderate yield. A marginal increase in the yield was noticed when the reaction was done under an oxygen atmosphere (Scheme ) 17 …”
Section: Reactions Involving Carbon−carbon Bond Formationmentioning
confidence: 99%
“…Along similar lines, CAN-mediated oxidative cyclization of cinnamyl ethers 352 and 354 gives SCHEME 76 SCHEME 77 rise to 3,4-trans-disubstituted THF derivatives 353 and 355, respectively, with a high stereospecificity (Scheme 80) [172].…”
Section: Scheme 74 Scheme 75mentioning
confidence: 90%
“…Under argon atmosphere, the reaction afforded the corresponding tetrahydrofuran derivatives as a mixture of methoxy and nitrato derivatives 71 and 72 in 2:1 ratio in high yields (Scheme 13). 82 It has been shown that homobenzylic ethers with pendant enolacetate moiety such as 73 can undergo highly efficient cleavage followed by 6-endo cyclization in the presence of CAN to afford tetrahydropyrone 74 with excellent stereocontrol. 83 5-endo Cyclization of enamide esters such as 75 in the presence of CAN led to disubstituted g-lactam 76 in moderate yields.…”
Section: Intramolecular Carbon-carbon Bond Forming Reactionsmentioning
confidence: 99%